Novel versatile topologies and design optimization of wide-bandstop frequency selective surfaces for X-band, Ku-band and millimeter-wave applications - Rao Shahid Aziz; Slawomir Koziel; Leifur Leifsson; Stanislaw Szczepanski (Scientific Reports, 2023)
Abstract Novel designs of frequency selective surface (FSS) are presented for wideband applications in X, Ku and mmWave (millimeter Wave) bands. Two identical metallic layers of FSS are imprinted on both sides of the RO4003 substrate. The geometry parameters are optimized to maximize the bandstop at the specified in-band maximum transmission level of −10 dB; satisfaction of the latter condition is enforced through appropriate formulation and handling of the design constraints. The proposed structure is versatile and can be readily re-designed for various operating bands. For the sake of illustration, two instances of the FSS were developed. Design 1 exhibits broad bandstop of 9.8 GHz at the X- and Ku-bands, whereas the bandstop of Design 2 is 33.5 GHz at the mmWave band. The two FSS unit cell designs share the same base topology, but specific dimensions are adjusted to operate within the lower and the higher bands, respectively. The unit cell is symmetrical, therefore, ensures an excellent resonance stability performance with respect to different polarizations (TE and TM) and incidence angles. For proof of concept only FSS Design 1 is fabricated and measured in an anechoic chamber. The simulated and measured results exhibit good agreement. Extensive benchmarking against state-of-the-art FSS designs from the literature corroborates the advantages of the proposed topology in terms of design novelty, topological versatility, compact size, and wide bandstop response as compared to the previously available designs.